2013
DOI: 10.3109/15368378.2013.801850
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of 900 MHz radiofrequency radiation emitted from mobile phone on testicular tissue and epididymal semen quality

Abstract: The purpose of this study is to bridge this gap by investigating effects of long term 900 MHz mobile phone exposure on reproductive organs of male rats. The study was carried out on 14 adult Wistar Albino rats by dividing them randomly into two groups (n: 7) as sham group and exposure group. Rats were exposed to 900 MHz radiofrequency (RF) radiation emitted from a GSM signal generator. Point, 1 g and 10 g specific absorption rate (SAR) levels of testis and prostate were found as 0.0623 W/kg, 0.0445 W/kg and 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 30 publications
2
18
1
Order By: Relevance
“…Indeed, in a majority of studies reporting negative impacts of RF-EMR on sperm motility (64%), the study design featured the use of isolated human spermatozoa that were exposed to RF-EMR via a mobile phone device. In contrast, at least half of the instances in which no effect was recorded on sperm motility, the studies involved whole-body animal exposure using a signal generator to produce the RF-EMR (Aitken et al 2005, Trosic et al 2013, Tas et al 2014. Although these data further lend support to our proposal of spermatozoa as a sensitive model, they also highlight that in vivo, the body may be capable of absorbing some of this radiation (Fig.…”
Section: R268contrasting
confidence: 34%
See 3 more Smart Citations
“…Indeed, in a majority of studies reporting negative impacts of RF-EMR on sperm motility (64%), the study design featured the use of isolated human spermatozoa that were exposed to RF-EMR via a mobile phone device. In contrast, at least half of the instances in which no effect was recorded on sperm motility, the studies involved whole-body animal exposure using a signal generator to produce the RF-EMR (Aitken et al 2005, Trosic et al 2013, Tas et al 2014. Although these data further lend support to our proposal of spermatozoa as a sensitive model, they also highlight that in vivo, the body may be capable of absorbing some of this radiation (Fig.…”
Section: R268contrasting
confidence: 34%
“…In general, these data lend support to the notion that RF-EMR can significantly impair key aspects of sperm function including the motility and vitality of these cells and the integrity of their DNA (Table 1), suggesting a direct effect on mature spermatozoa. However, there is less compelling evidence to suggest an additional role at the level of spermatogenesis in reducing sperm counts in vivo (Imai et al 2011, Tas et al 2014. Indeed, a chronic, multigenerational study demonstrated RF-EMR to have no effects on sperm production and testicular or epididymal weight (Sommer et al 2009).…”
Section: The Impact Of Rf-emr On Semen Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…They also stated that the weights of testis, epididymis, prostate and vesiculoseminalis did not change, and there was not a statistically signifi cant difference in sperm concentration and motility (23). Again, in another study, following the exposure of 1900 MHz RF radiation for 60 minutes/day for a period of 14 days, expansion in seminiferous tubule, karyomegaly in some spermatogenic nuclei and degeneration of non-spermatozoa seminiferous tubules were observed (24).…”
Section: Discussionmentioning
confidence: 94%